Development of Interactive Digital Learning Materials for the Textile Technology Course - Ulfa Annida Damanik; Fitri Amaliyah Batubara; Halimul Bahri; Eka Rahma Dewi; Yudhistira Anggraini (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study aimed to develop a valid Textile Technology learning e-module. The research employed a research and development (R&D) approach, focusing on the development of a Textile Technology learning e-module product. The development model applied in this study was the Instructional Development Institute (IDI) model. The research subjects consisted of FT Unimed students enrolled in the Textile Technology course. Data were collected using a questionnaire, while descriptive data analysis was employed to determine the feasibility of the Textile Technology e-module. The findings revealed that: (1) a Textile Technology learning e-module was successfully developed, and (2) the developed e-module was categorized as highly valid in terms of material aspects (0.90) and format aspects (0.82). Based on these findings, it can be concluded that the Textile Technology e-module is feasible for use as a learning module in Textile Technology courses at the higher education level.